ACADEMIC WRITING OFFICE OF SOUTH URAL STATE UNIVERSITY: GOALS, STRUCTURE, FUNCTIONING - M. A. Chernysheva; E. A. Nenakhova; E. V. Donova (Высшее образование в России, 2017)
The article focuses on describing the structure and functional characteristics ofthe Academic Writing Office of South Ural State University (National Research University), member of the project 5-100, which provides for increasing competitive ability of Russian universities in the global research and education market. The Office aims to improve the academicians and postgraduate students' writing skills in English and to support those authors wishing to publish their papers in high-ranking scientific journals indexed in scientometric databases Scopus and Web of Science. The implementation of the goals of Academic Writing Office of South Ural State University (SUSU) is assured by the interaction of its administrative, consulting, translating and educational blocks supported by Office official site.